Nilai Budaya dalam Novel â€œAssalamualaikum Beijingâ€ Karya Asma Nadia sebagai Alternatif Pembelajaran Sastra di SMA/MA - Hartati, Diyah Widi (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This research is aimed to find culture value from the novel entitled ?Assalamualaikum Beijing? which wrote by Asma Nadia found on intrinsic element as well as ekstrinsic. To reach that goal, researcher used text in interpretation theory by the description method, the facts like the words in the quote and continued with the analyzing to give understanding and explanation. The research approach that is used based on the genetic structuralism a study about among the many factor relationship, built from intrinsic, extrinsic factor and the author. This research output show that the novel ?Assalamu? alaikum Beijing? by Asma Nadia has a lot of culture value elements. That culture values are language, knowledge system, social organization, equipment life and technology system, the system of livelihood, religion system, and art. There is element of social organitations value in this novel but it?s not knotted clearly. The developing of culture values by background, character, and language that are used in the story. Those culture values found on intrinsic element as well as novel ekstrinsic which is direct or indirect. ?Assalamualaikum Beijing? novel can be implicated as one of alternative learning for literature in Senior High School level. The results of this study can be implicated as material for teaching literature ini Senior High School (SMA/MA).